Customer loyalty towards Tesco hypermarket Malacca / Fathilah Mohamed Aris - Mohamed Aris, Fathilah (Faculty of Business and Management, 2007)
Loyalty is the crucial element for every organization. The elements of creating the loyalty among the customers are trust, communication, satisfaction, value, brand affect, brand equity, conflict handling, commitment, and resistance to change. These factors may influence the existing customers to become loyalty to the firm whereby it will determines how far the firms can go and how long do the firms can sustained in the marketplace. It will be an advantage to the firms if they are able to build strong customer loyalty among the customers.